Evristica as high-developed logical thought - Ремзі, І. В.; Сідельнікова, В. К.; Гапон, В. І. (Scientific notes of the pedagogical department, 2017)
In the article by interdisciplinary analogical way the modal of the evristic stage within a creative person’s thought is proposed. On the ground of relationship logical and creative within person’s thought the basis of technologies to train students for universal thought is propounded.